2018
DOI: 10.1371/journal.pone.0204886
|View full text |Cite
|
Sign up to set email alerts
|

Reducing attrition within clinical trials: The communication of retention and withdrawal within patient information leaflets

Abstract: BackgroundThe recruitment and retention of patients are significant methodological challenges for trials. Whilst research has focussed on recruitment, the failure to retain recruited patients and collect outcome data can lead to additional problems and potentially biased results. Research to identify effective retention strategies has focussed on influencing patient behaviour through incentives, reminders and alleviating patient burden, but has not sought to improve patient understanding of the importance of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 43 publications
3
35
0
Order By: Relevance
“…Our findings resonate with data from a recent study that analysed 50 patient information leaflets (PILs) for clinical trials across a cohort of publically funded UK based RCTs [7]. This analysis of PILs identified that retention is often poorly described within this written information with an unbalanced focus on the patients right to withdraw (present in 98% of the PILs analysed) without having to give a reason (90%) [7]. Contrastingly, only 16% of the PILs analysed included statements on the value and importance of retention [7].…”
Section: Key Findingssupporting
confidence: 86%
See 2 more Smart Citations
“…Our findings resonate with data from a recent study that analysed 50 patient information leaflets (PILs) for clinical trials across a cohort of publically funded UK based RCTs [7]. This analysis of PILs identified that retention is often poorly described within this written information with an unbalanced focus on the patients right to withdraw (present in 98% of the PILs analysed) without having to give a reason (90%) [7]. Contrastingly, only 16% of the PILs analysed included statements on the value and importance of retention [7].…”
Section: Key Findingssupporting
confidence: 86%
“…Analysis first took a deductive approach and entailed coding data transcripts into predefined categorical descriptions (such as 'presence of discussion of retention', discussion of questionnaires', 'discussion of withdrawal', etc) taking a constant comparative approach. The pre-defined codes were developed by all members of the research team based on research aims and informed by existing literature on information that may be important for retention [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditional lottery tickets and monetary incentives have been successful in increasing response rates to online questionnaires and retention in randomized trials [30]. Another possibility is to emphasize the importance of retention and how the participants can make valuable contributions to improve care for pregnant women in the Patient Information Leaflet [31].…”
Section: Discussionmentioning
confidence: 99%
“…The failure of retaining recruited participants can lead to potentially biased results. 9 Effective retention strategies can be based on influencing participants' behaviour through incentives, reminders, or alleviating participants' burden, and should include the improvement in participant's understanding of the importance of retention 9 . The schedule of too many visits/procedures, a long-distance between participants' home and study site, and doubts/questions about the frequency/occurrence of adverse events are some of the reasons for participant's withdrawal.…”
Section: Study Participants Recruitment and Retentionmentioning
confidence: 99%